Impact of asymmetric dimethylarginine on mortality after acute myocardial infarction - Zeller, Marianne; Korandji, Claudia; Guilland, Jean-Claude; Sicard, Pierre; Vergely, Catherine; Lorgis, Luc; Beer, Jean-Claude; Duvillard, Laurence; Lagrost, Anne-Cécile; Moreau, Daniel; Gambert, Philippe; Cottin, Yves; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2008)
Asymmetrical dimethylarginine (ADMA) is an endogenous competitive inhibitor of nitric oxide (NO) synthases. From a prospective cohort of patients with acute myocardial infarction (MI), we aimed to analyze the predictive value of circulating ADMA concentrations on prognosis. Blood samples from 249 consecutive patients hospitalized for acute MI <24 hours were taken on admission. Serum levels of ADMA and its stereoisomer, symmetrical dimethylarginine (SDMA), were determined using high-performance liquid chromatography. The independent predictors of ADMA were glomerular filtration rate, female sex, and SDMA (R(2)=0. 25). Baseline ADMA levels were higher in patients who had died than in patients who were alive at 1 year follow-up (1.23 [0.98 to 1.56] versus 0.95 [0.77 to 1.20] micromol/L, P<0.001). By Cox multivariate analysis, the higher tertile of ADMA (median [interquartile range]: 1.45 [1.24 to 1.70] micromol/L) was a predictor for mortality (Hazard Ratio [95% CI], 4.83 [1.59 to 14.71]), when compared to lower tertiles, even when adjusted for potential confounders, such as acute therapy, biological, and clinical factors. Our study suggests that the baseline ADMA level has a strong prognostic value for mortality after MI, beyond traditional risk factors and biomarkers.